Simulation of seepage flow of non-aqueous phase liquid in vadose zone. Issue 3 (June 2017) - Kikumoto, Mamoru; Nakamura, Keita
Abstract : A comprehensive numerical method for simulating transport of non-aqueous phase liquids (NAPLs) in unsaturated subsurface was developed based on a novel capillary pressure-saturation model for three-phase water-NAPL-air in soils. In the method, weak forms of the mass balance equations for water, NAPL and air were discretised in space using the Galerkin method and were discretised in time using the implicit backward Euler method. A modified Picard iteration scheme was implemented to deal with the non-linearity of the governing equations and to keep the mass balance of three fluids. The method properly takes into account the interactions among three-phase fluids in soils and is capable of describing the capillary behaviour of NAPL in unsaturated soils. The methodology developed was applied to some initial value problems of NAPL leakage into the vadose zone. A one-dimensional leakage simulation of NAPL that is less dense than water (LNAPL) validated that the proposed method predicts the realistic penetration behaviour of NAPLs into an unsaturated subsurface. Furthermore, two-dimensional simulations on leakage of LNAPL and NAPLs that are denser than water (DNAPL) into an unsaturated ground containing impermeable layers confirmed that the proposed analysis method is capable of representing the contamination process in shallow ground, including differences in the penetration mechanisms of LNAPL and DNAPL.